Limited value of vaginal cytology in detecting recurrent disease after radical hysterectomy for early stage cervical carcinoma - Napat Injumpa (2018)
The objective of this study was to evaluate the value of vaginal cytology in routine surveillance for recurrent cervical cancer after surgery. We reviewed the medical records of 565 patients with stage IB-IIA cervical cancer who were treated with radical hysterectomy and pelvic lymphadenectomy (RHPL) and attended follow- up at Chiang Mai University Hospital between January 2000 and May 2006. With the median follow-up of 35 months (range 1-76 months), 23 (4%) patients developed recurrence. The interval from surgery to detection of recurrence ranged from 5-61 months with a median of 23 months. Of the total 4,376 vaginal smears, 5 (0.1%) showed abnormal cytology but only 1 had malignant cells and tumor recurrence. The sensitivity and specificity of vaginal cytology for detection of recurrence were 4.3% and 99.3%, respectively. In conclusion, vaginal cytology has limited value in detection of recurrence after RHPL for early-stage cervical cancer.